Troy [videorecording (DVD)] - Petersen, Wolfgang; Pitt, Brad, 1963-; Bana, Eric; Bloom, Orlando, 1977-; Homer (Warner Home Video, 2004)
In 1193 B.C., Prince Paris, the son of the King of Troy falls in love with Helen, the wife of the king of Sparta, and convinces her to follow him away from her husband, Menelaus, the result is an epic war. The Greeks sail to Troy and lay siege. Achilles, the greatest warrior in all the world, is called in to fight against Troy and give Greece the upper hand. Hector, the eldest son of Priam, King of Troy, and the greatest Trojan warrior embodies the hopes of the people of his city.